Prevalence of HPV infection by cytologic diagnosis and HPV DNA extraction and prevalence of the HPV genotypes detected in urban Turkish women - YOLDEMİR, AHMET TEVFİK (WILEY, 2010)
Objective: To evaluate the prevalence of the different human papillomavirus (HPV) genotypes in women seen at 2 Marmara University Hospital gynecologic outpatient clinics in Istanbul, Turkey. Methods: From May 1 through August 31, 2008, specimens were obtained from 500 women for cytologic evaluation by the split-sample method. HPV types were identified by PCR and hybridization using a microarray that identifies 35 types. Results: The overall prevalence of HPV was 16.5%, multiple genotypes were found in 35.8% of the infected women, and 75% of the types were high risk; 79% of the infected women had negative cytologic results, 3.7% had ASCUS, 10% had LSIL, and 6% had HSIL; the highest infection rates were 36% for women aged 20 to 30 years and 35% for those aged 31 to 40 years; 65.2% of the infected women were university graduates; and 34% were single. Conclusion: HPV infection involved numerous types, most of them high risk, even in women with negative cytology results. Further studies with larger groups will provide more information on HPV distribution in Turkey, which may guide the development of local vaccination programs. (C) 2010 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Cervical Cytology; HPV genotype; HPV prevalence; HUMAN-PAPILLOMAVIRUS; CERVICAL-CANCER; MICROARRAY; RISK; FEMALES; LESIONS